PENGARUH STRATEGI PEMBELAJARAN AFEKTIF TERHADAP SIKAP SOSIAL SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS VIII DI MTSN 1 KUANTAN SINGINGI (TP.2021/2022) - Winda Puspita Dilla; Andrizal Andrizal; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
This research is motivated by an Affective learning strategy which has the main goal of being able to make decisions based on values ​​that are considered good. In fact, students still lack social attitudes. Social attitude is an individual's tendency to take an action. The response that occurs in attitude is a consistent response. Attitude is reflected in the behavior or actions of each individual. If a person behaves well, it can be said that his attitude is good. Social Attitudes of Students in the Subject of Aqidah Akhlak Class VIII at MTSN 1 Kuantan Singingi (TP.2021/2022). This research is a causal associative research, which was conducted at MTSN 1 Kuantan Singingi. The data collection technique used was a questionnaire with instruments in the form of questionnaires, interviews, observation and documentation. Data analysis used the SPSS for Window Release 21.0 program. The results showed that there was a positive and significant effect of the affective learning strategy on the significance test found the equation that the value (sig.) 0.03 < than the probability of 0.05 so it was concluded that there was an effect of variable X on Y.